Rare bird documentation form for Greater Scaup at Lake Manawa, 1981 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1981)
Rare bird documentation form for a Greater Scaup at Lake Manawa in Pottawattamie County, IA on March 24, 1981. Epson - sheet feed